CONSISTENCY OF MANAGEMENT AS THE MAIN IMPERATIVE IN THE TRANSITION TOWARDS SUSTAINABLE DEVELOPMENT - A. A. Nikonova (Стратегические решения и риск-менеджмент)
Key Russian economics challenges and opportunities to effective use her competitive advantages are discussed in the publication. Some critical system management requirements are formulated to transit the Russian economy to a more sustainable growth. Presented applications of system theory fundamentals are intended to the choose directions and adequate regulatory mechanisms to promote sustainable economic growth in situation of turbulence.